Purity and prejudice: deluding ourselves about biodiversity conservation - Sheil, Douglas; Meijaard, E. (2010)
Tropical conservationists can benefit from understanding human thought processes. We are often less rational than we might believe. Our judgmental biases may sometimes encourage us to overlook or act against major conservation opportunities. Better appreciation of the tricks of the human mind might make us more open-minded, humble, and ready to appreciate different viewpoints. We propose one inherent bias that we believe predisposes conservationists to neglect the value of modified habitats for biodiversity conservation. We call it the ‘tainted-nature delusion’. Recognizing such biases can increase our effectiveness in recognizing and achieving viable conservation outcomes.